AAC Models and Classification Systems - Fuller, Donald R.; Pampoulou, Eliada; Lloyd, Lyle L. (My University, 2024)
Models and classification systems are important only for researchers and theorists to understand. As an educator/clinician, models and taxonomies have no relevance to my daily practice.